(untitled) (Third Sector Social Economic Review, 2019)
Universities provide significant contributions to both economy and development of region in which universities are built up. The main functions of universities are research and development and education however they revitalize the economy of their region and help development of region. This research aims to investigate contribution of Kastamonu university to city economics. At the end of this research static direct, indirect and induced income and employment impacts of Kastamonu university are obtained and the importance of its’ role on city economy is understood.